Content Analysis of Science Education Research in Special Education Journals - Seraceddin Levent Zorluoğlu; Gamze Devecioğlu; Aydın Kızılaslan (Journal of Science Learning, 2022)
This study examines the special education studies on science education in the ERIC database. The main facts to be determined in the content analysis conducted in this study are as follows: subject types of special education studies in the field of science education, change of preferred studies according to years, main objectives, research methods, sample sizes, data collection tools, research method, data analysis method, the types of disabilities of the individuals in the samples, the level of education of the participants, the types of techniques used in the analyses. The articles reviewed in the study were searched in ERIC databases. As a result of the search, 87 articles were examined within the scope of science and special education in nineteen journals. Tables and figures were used to make the findings more understandable. According to study results: It has been concluded that both researchers working in the field of special education and researchers working in the field of science education do not want to conduct science education studies with individuals with special needs; the special education studies mainly were conducted in the field of science and technology; the studies were mainly focused to STEM; it was determined that the most studies were done in the field of science education and the least in the field of physics, chemistry, and astronomy; "Quasi-experimental" and "Multiple design" methods were preferred the most among the quantitative research methods.